Nitrogen retention capacity of paddy soil improved under long-term garlic-rice rotation - Wei Zhou; Yanqiu Chen; Zhitao Hu; Yu Fan; Yihong Kuang; Tao Wang; Yong Chen; Fei Deng; Xiaolong Lei; Jianfeng Hu; Youfeng Tao; Hong Cheng; et al. (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2023)
Although significant differences in soil nitrogen levels exist under different paddy-upland rotations, the main reason for this is unclear. The nitrogen retention capacity and loss of ammonia volatilisation, leaching, etc. of paddy soil with large differences in nitrogen levels from two long-term rotations, garlic-rice and wheat-rice, were measured using the soil column simulation method. The results showed that the loss rate of leaching was only 5.4%, whereas that of ammonia volatilisation was up to 22.8%, which was the main nitrogen loss way of paddy soil under the two rotations. The average ammonia volatilisation rates under wheat-rice rotation with high and low nitrogen application rates were 12.1% and 40.2% higher than that under garlic-rice rotation, leading to a decrease in the total nitrogen loss amount and rate through ammonia volatilisation by 29.8% and 8.8%, respectively. As a result, nitrogen retention in the soil under garlic-rice rotation increased by 12.7%. In conclusion, the long-term garlic-rice rotation could significantly inhibit ammonia volatilisation, thus improving the soil nitrogen retention capacity. The straw return may increase soil organic matter content, reduce ammonia volatilisation loss, and enhance soil nitrogen retention capacity and productivity.